PENGARUH ROTASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. ASTRA HONDA MOTOR PLANT 3 CIKARANG - Ahmad Maulana; Devi Krisnawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
To determine the effect of work rotation and organizational culture on the performance of employees of PT. Astra Honda Motor Plant 3 Cikarang. This research is included in the category of causal associative research using a quantitative approach. The population in this study is limited to the Warehouse 4 Plant 3 Cikarang (P3WH4) section which has obtained permission from the Head of Section P3WH4. Where the population is 48 people, the sampling technique uses saturated sampling technique, while the data analysis method uses partially and simultaneous linear regression. The results showed that partially or simultaneous work rotation and organizational culture had a positive and significant effect on the performance of the employees of PT. Astra Honda Motor Plant 3 Cikarang.